From Endodontic Therapy to Regenerative Endodontics: New Wine in Old Bottles - Lim, Ghee S.; Wey, Mang C.; Azami, Noor H.; Noor, Nora S.M.; Lau, May N.; Haque, Nazmul; Govindasamy, Vijayendran; Kasim, Noor H. A. (Current Stem Cell Research & Therapy, 2021)
The concept of regenerative endodontics wherein one can replace damaged pulp structures and recuperate the functionality in erstwhile necrotic and infected root canal systems has been a cutting-edge technology. Though the notion started as early as the 1960s, even before the discovery of stem cells and regenerative medicine, it was in the 2000s that this procedure gained momentum. Ever since then, researchers continue to discover its essential benefit to immature teeth and its ability to overcome the caveats of endodontic therapy, which is commonly known as root canal treatment. Further, through this therapy, one can redevelop root even in immature teeth with necrotic pulps, which overall helps in maintaining skeletal and dental development. Past literature indicates that regenerative endodontic procedures seem to be successful, especially when compared with other conventional techniques such as Mineral Trioxide Aggregate apexification. Besides, many clinicians have begun to apply regenerative endodontic procedures to mature teeth in adult patients, with several clinical case reports that have shown complete resolution of signs and symptoms of pulp necrosis. Generally, the three most desirable outcomes anticipated by clinicians from this procedure include resolution of clinical signs and symptoms, root maturation and redevelopment of the neurogenesis process. Despite this, whether these objectives and true regeneration of the pulp/dentin complex are achieved is still a question mark. Following the discovery that regenerative endodontics indeed is a stem cell-based treatment, addressing the fundamental issue surrounding stem cells might assist in achieving all identified clinical outcomes while favoring tissue formation that closely resembles the pulp-dentin complex.
Keywords: mature teeth